2016
DOI: 10.2807/1560-7917.es.2016.21.25.30262
|View full text |Cite
|
Sign up to set email alerts
|

Active surveillance scheme in three Romanian hospitals reveals a high prevalence and variety of carbapenamase-producing Gram-negative bacteria: a pilot study, December 2014 to May 2015

Abstract: We report the findings of an active surveillance scheme for detection of asymptomatic carriers with carbapenemase-producing Gram-negative bacteria (CP-GNB) in Romanian hospitals. During a pilot study from December 2014 to May 2015, faecal cultures were screened in three hospitals (two large, one medium-size) for patients newly admitted to selected wards or inpatients transferred from other wards to an intensive-care unit. The study revealed a high prevalence of CP-GNB detected in 22/27 and 28/38 of the carbape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…The MIC value for carbapenems is also higher in OXA-48 producers when an ESBL production is associated. (15) Several articles published in the last years signaled the presence of OXA-48 K. pneumoniae isolates starting with 2010 in patients admitted in hospitals from different cities in Romania (16)(17)(18)(19). We described the first cases of OXA-48 K. pneumoniae infections diagnosed in our hospital.…”
Section: Discussionmentioning
confidence: 83%
“…The MIC value for carbapenems is also higher in OXA-48 producers when an ESBL production is associated. (15) Several articles published in the last years signaled the presence of OXA-48 K. pneumoniae isolates starting with 2010 in patients admitted in hospitals from different cities in Romania (16)(17)(18)(19). We described the first cases of OXA-48 K. pneumoniae infections diagnosed in our hospital.…”
Section: Discussionmentioning
confidence: 83%
“…The majority (239/265 [90.2%]) of OXA-48-positive isolates were found to be K. pneumoniae, E. coli, and E. cloacae, with dissemination to the greatest number of additional species observed among isolates from Turkey, one of the main reservoirs of bla OXA-48 (5,6). A total of 64.9% (172/265) of all OXA-48-positive isolates were collected in countries in which endemic (Turkey), interregional (Belgium, France, Romania, and Spain), or regional (Germany and Italy) spread of OXA-48 was recently reported (25,48,49). An additional 27.5% (73/265) of isolates were collected from multiple medical centers in Russia; though limited information regarding the epidemiology of carbapenemase-producing Enterobacteriaceae is available for this country, presumed interspecies and interpatient spread of bla OXA-48 was reported during a 2-year period in a hospital intensive care unit located in Moscow (50).…”
Section: Discussionmentioning
confidence: 99%
“…More recently one study from our department highlights a remarkable mobility for bla OXA-23 -Tn2008 and surrounding structures (identified in plasmid or chromosome of different clones) and also describes for the first time the spread of Tnaph6-carrying pACICU2-like plasmids in A. baumannii in Europe [27]. A pilot study from three Romanian hospitals -Iasi and Targu-Mures (2014-2015) demonstrated the presence of carbapenemases OXA-23, OXA-24/72 in A. baumannii nosocomial isolates [38].…”
Section: Resultsmentioning
confidence: 82%